Influence of rooting media on mycorrhizal development and nutrient contents in marigold - VIJAY, J.; DORAJEERAO, A.V.D. (Journal of Ornamental Horticulture, 2025)
An experiment was carried in factorial concept with two factors i.e., varieties at two levels and rooting media at eight levels thus making 16 combinations which were replicated twice. The effect of varieties, rooting media and their interactions were found to be significant on different mycorrhizal and nutrient content parameters. Among the rooting media, the maximum mycorrhizal spore count in root zone (197) was recorded by M8 - soil : vermicompost : coco peat : saw dust (1:1:1:1) v/v + mycorrhiza on par with M6 - soil : vermicompost : coco peat : rice husk (1:1:1:1) v/v + mycorrhiza (186). Relative Microbial Dependency Index was also observed to be higher with the above media. The highest nitrogen uptake (136.09 kg ha–1) was recorded by M6 - soil : vermicompost : coco peat : rice husk (1:1:1:1) v/v + mycorrhiza followed by M8 - soil : vermicompost : coco peat : saw dust (1:1:1:1) v/v + mycorrhiza (135.47 kg ha–1) followed by M4 - soil : vermicompost : coco peat (1:1:1) v/v + mycorrhiza (113.76 kg ha–1). The lowest nitrogen uptake was observed for M1 - soil. (57.69 kg/ha).